Effect of Self-Etching and Single-Bottle Bonding Systems On Shear Bond Strength of Fissure sealant to Primary and Permanent Enamel - Sara Tavassoli Hojjati; Majid Mehran; Tayebeh Noori Etemad; Roshanak Montazeri Hedeshi (Islamic Dental Association of Iran, 2014)
Background and Aim: Application of self-etching bonding systems to primary and permanent teeth has increased due to the simplicity of work and fewer steps. This experimental study aimed to compare the effect of conventional acid etching and single-bottle and self-etching bonding systems on shear bond strength (SBS) of light-cured fissure sealant to primary and permanent enamel .   Materials and Methods: In this experimental study, the smoothest unprepared proximal enamel surfaces of 30 primary molars (groups 2, 4 and 6) and 30 permanent premolar teeth (groups 1, 3 and 5) were divided into 6 groups of 10. Groups 1 and 2 (control) were acid-etched and received light-cured fissure sealant (Concise 3M-ESPE). Groups 3 and 4 (SB) were subjected to acid etching + Single Bondadhesive + fissure sealant. Groups 5 and 6 (PLP) received self-etching bonding system (Prompt L-Pop, 3M, ESPE) + fissure sealant. Specimens were then subjected to 500 thermal cycles with the dwell time of 30 seconds. Shear bond strength was determined using Universal Testing Machine (Zwick, Germany). Mode of fracture was determined under stereomicroscope and data were analyzed using ANOVA, (between-subjects effect) and LSD .   Results: SBS was not significantly different between the control and PLP or SB and PLP groups (P>0.05). However, the difference in SBS between the control and SB groups was statistically significant (P=0.022). The SBS in primary teeth was less than in permanent teeth in all groups (P<0.05 ).   Conclusion: Self-etching bonding system (PLP), similar to conventional acid etching technique, provides adequate bond between the light-cured fissure sealant and unprepared enamel. Application of Single Bond Adhesiveeffectively increased the fissure sealant bond strength .